The Effect Of ABPK KB Module Education On Long-Term Contraceptive Methods On The Level Of Women Of Childbearing Age Knowledge - Ade Krisna Ginting; Marini Iskandar; Sifa Humaida; Alfaura . (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Based on the 2017 IDHS data, that 44% of currently married women use a family planning method/method, 57% percent use modern family planning tools/methods, only 5% use implant family planning, 5% IUD, and 4% MOW). In addition, based on SKAP 2019 data, the use of the Long-Term Contraceptive Method (MKJP) is also still low, at 24.6%. The aim of the study was to increase the knowledge of women of childbearing age related to MKJP by using the ABPK KB module in the Kedungwaringin area. The research method used is an experiment with a quasi-experimental technique, using a one group pre and posttest design approach. The population and sample were adjusted according to the inclusion and exclusion criteria in the study. Sampling technique with total sampling, with a sample of 51 respondents. The research instrument used is a questionnaire. The research was carried out in the Kedungwaringin sub-district in July – August 2022. The statistical test was carried out using the Wilcoxon test. The results of the study, before being given education using the ABPK KB MKJP module, the average level of WUS knowledge with a mean value of 56.92 and after being given education using the MKJP APBK KB module the average level of WUS knowledge increased with a mean value of 84.92. The results of the Wilcoxon test found that there was a significant effect between WUS knowledge about MKJP, p value = 0.000 (? <0.05.) The conclusion in this study was that there was a significant effect between WUS knowledge about MKJP before and after being given counseling with the APBK KB module. It is hoped that midwives can use the APBK KB module when providing education about MKJP, thus it is hoped that WUS will get good information about MKJP so that it will be easier for WUS to choose contraception according to their needs, which in the end is expected to improve family quality by creating small happy and prosperous families.